2013
DOI: 10.1111/pbr.12089
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the genetic base of lentil cultivars through inter‐sub‐specific and interspecific crosses of Lens taxa

Abstract: Wild Lens taxa are invaluable sources of useful traits for broadening genetic base of cultivated lentil. Nine inter-sub-specific and interspecific crosses were made successfully between cultivated (Lens culinaris ssp. culinaris) and wild lentils (L. culinaris ssp. orientalis, odemensis, lamottei and ervoides). The effect of species groups, day length and temperature on crossability in lentils was evident under normal winter sowing in New Delhi and in summer Himalayan nursery at Sangla in Himachal Pradesh, Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…wild species including L. culinaris ssp. orientalis , odemensis , lamottei and ervoides) has substantially exhibited higher variations for seed yield and its attributing traits in segregating F 2 generation indicating transgressive segregation (Gupta and Sharma 2007;Singh et al 2013). …”
Section: Assessment Of Diversification Of Indian Gene Poolmentioning
confidence: 99%
“…wild species including L. culinaris ssp. orientalis , odemensis , lamottei and ervoides) has substantially exhibited higher variations for seed yield and its attributing traits in segregating F 2 generation indicating transgressive segregation (Gupta and Sharma 2007;Singh et al 2013). …”
Section: Assessment Of Diversification Of Indian Gene Poolmentioning
confidence: 99%
“…The incorporation of potential gene sources from L. ervoides is highly desirable, because they possess genes for adaptive variation and Fusarium wilt resistance and may further produce other higher yielding derivatives upon hybridization with cultigens, other than we already achieved in the current study. Furthermore, the common better performing F 5 recombinant lines selected from Delhi and Shimla centers reveals their wider adaptation and potential for developing high yielding cultivars of lentil and these lines can also be utilized as donors for further cross- breeding purposes in lentil genetic improvement (Singh et al, 2013; Tullu et al, 2013). The review of literature pertinent on widening the genetic base of cultivated lentil in relation to transferring resistance from wild Lens species against anthracnose (Fiala, 2006; Tullu et al, 2006; Fiala et al, 2009; Vail and Vandenberg, 2011; Vail et al, 2012), ascochyta blight (Tullu et al, 2010), Stemphylium blight (Podder et al, 2013) and yield attributes (Gupta and Sharma, 2006, 2007; Singh et al, 2013) have been successfully attempted.…”
Section: Discussionmentioning
confidence: 99%
“…As has already been discussed previously, intraspecifi c crosses between cultivated lentils produce viable descendants (Malhorta et al 1978 ;Solh et al 1980 ;Mera and Erskine 1982 ;Kumar and Singh 1998 ;Fratini et al 2004 ;Singh et al 2013b ). With regard to inter-subspecifi c hybrids of lentil, it has been reported that the domesticated lentil is readily crossable with subspecies orientalis (Ladizinsky 1979 ;Muehlbauer et al 1989 ;Vandenberg and Slinkard 1989 ;Vaillancourt and Slinkard 1992 ;Fratini et al 2004 ), although the fertility of the hybrids depends on the chromosome arrangement of the wild parent (Ladizinsky 1979 ;Ladizinsky et al 1984 ).…”
Section: Interspecifi C Hybridization In Crop Speciesmentioning
confidence: 92%